Acute Myocardial Infarction and Community-acquired Staphylococcus aureus Bloodstream Infection: An Observational Cohort Study. (14th August 2020) - McNamara, John F; Harris, Patrick N A; Chatfield, Mark D; Paterson, David L
Abstract: Background: The relationship between acute myocardial infarction and infection was recognized in the early 20 th century during influenza epidemics. Most recently, a case control study and a self-control design study have identified an association between Staphylococcus aureus infection and acute myocardial infarction. We assessed the association of community-acquired Staphylococcus aureus bloodstream infection (CA-SABSI) and myocardial infarction in the 365 days following blood culture. Methods: This was a cohort study assessing the incidence of myocardial infarction 365 days after blood culture for Staphylococcus aureus . Culture-negative patients had blood cultures collected at hospital attendance and were matched to the CA-SABSI participants by sex, 5-year age strata, and year of culture collection. Pathology information was linked to hospital administrative data and index of relative socioeconomic advantage and disadvantage (ISRAD). Results: The study included 5157 CA-SABSI cases matched to 10 146 blood culture–negative cases. The mortality rate was significantly higher in the CA-SABSI group (10.9%; 562/5157) than in culture-negative cases (5.1%; 521/10 146) at 365 days ( P  < .0001). In the 7 days following the index blood culture, excluding recurrent events, there were 89 (1.7%) and 37 (.4%) myocardial infarction diagnoses in the CA-SABSI and culture-negative cases, respectively. Multivariable logistic regression for myocardial infarction demonstrated a significant association with CA-SABSI after adjusting for known risk factors (odds ratio [OR], 5; 95% confidence interval [CI], 3.3–7.5; P  < .0001). Myocardial infarctions occurring in this short-term risk period were associated with all-cause mortality in a Cox proportional hazard model (OR, 1.7; 95% CI, 1.2–2.4; P  < .005). Conclusions: CA-SABSI is associated with an increased short-term risk of myocardial infarction, which is associated with subsequent mortality. Abstract : Acute infections have been associated with cardiovascular events since the influenza epidemic of the early 20 th century. This study identified an acute association with myocardial infarction and Staphylococcus aureus bloodstream infection. These acute myocardial infarctions were associated with all-cause mortality.